(untitled) (Journal of the College of Education for Women, 2019)
Money matters exert a considerable influence on man’s life-style, socialrank and his relationship with other people. This paper aims at exploring the impactof money matters on the characters’ inner feelings, social status, and personalrelationships in Muriel Spark’s modern novel The Ballad Of Peckham Rye. Thispaper aspires to show that Spark’s subtle portrayal of characters reveals thedominance of money matters over human and social relationships.Muriel Spark ( 1918-2006) is a modern Scottish novelist whose wit anddetached sense of humour has brought her prolific body of both popular and criticalacclaim. Spark is interested not in building suspense but in exploring the moralsignificance of the characters’ actions. In addition, she chooses to depict thecharacters in her novels as individuals rather than as types; and she believes that itis the artist’s job to reveal the truth about the characters . Thus, Spark exposes theweaknesses and moral corruption of the characters as they confront with the realityof their existence. In an interview broadcasted by the B. B.C, Spark explains thatthere is a truth or a serious theme behind her fictional works and characters:I don’t claim that my novels are truth . . .I claim that they are fiction,out of which a kind of truth emerges. . . because I am interested in truthabsolutetruth. . . there is a metaphorical truth and a moral truth.